TRENDS IN THE DEVELOPMENT OF CRIMINAL LIABILITY FOR CRIMES AGAINST THE SECURITY OF COMPUTER INFORMATION IN THE RUSSIAN FEDERATION - V. Talan, Mariya; R. Gayfutdinov, Ramil (Gênero & Direito, 2019)
The development of modern computer technology and changes in federal legislation introduced in recent years, have caused the authors to identify the main trends in the development of criminal liability for crimes against the security of computer information: four areas that encourage the need to increase criminal liability for acts committed with computer technology. The paper also gives a historical overview devoted to the development of computer technologies and a general description of crimes in the field of computer information, taking into account changes introduced into criminal legislation by Federal Law No. 194-FZ dated July 26, 2017.